The Impact of Performance Measurement Systems on Employee Motivation and Productivity at Indonesia’s Defense University - Tatar Bonar Silitonga; Aloysius Sabon Payon; Manesi, Damianus (International Journal of Economics, Management and Accounting, 2025)
This ponder analyzes the impact of execution estimation framework on work inspiration and representative efficiency at the Staff of Military Coordinations, Indonesia Defense College, and tests the intervening part of work inspiration. The inquire about strategy employments a quantitative approach with a study of 125 respondents (teachers, scholastic staff, and bolster staff). Information were analyzed utilizing SEM. The comes about appeared that the execution estimation framework incorporates a positive and noteworthy impact on work inspiration (Î² = 0.52, p < 0.001), and work inspiration encompasses a positive impact on representative efficiency (Î² = 0.64, p < 0.001). Work inspiration moreover altogether intercedes the relationship between execution estimation framework and worker efficiency (Î² = 0.33, p < 0.01). This finding bolsters Self-Determination hypothesis which emphasizes the significance of satisfying mental must  increment natural inspiration. Show approval through the goodness-of-fit test appeared a great fit with the observational information (Chi-Square/df = 2.15, RMSEA = 0.06, CFI = 0.95, TLI = 0.93). For all intents and purposes, this ponder suggests an moved forward execution estimation framework that's  more transparent and reasonable to extend worker inspiration and efficiency. The investigate suggestions give hypothetical and commonsense commitments to the advancement of execution administration within the military and comparative organizations.